Google Translate Accuracy in Translating English Polysemy Words Found in Feature Articles - Immanuela Oktavianus, Grace; Xenia, Tia (Universitas Cokroaminoto Palopo, 2025)
Many previous studies evaluating the accuracy of Google Translate showed many issues and problems in the translation process through the variation of language pairs. However, those previous studies explored the general terms of accuracy, not one specific aspect of the translation output. Therefore, the present study aimed to evaluate the accuracy of Google Translate in translating English polysemous words found in the feature article. This study was conducted to foresee one specific area of semantics: polysemous words. Five feature article pairs that have already been published were used as the subject of this study. The data were all of the polysemous words found in the source text, divided into speech parts and the Google Translate output. These were evaluated using dictionaries of both languages to determine whether the meaning transferred was accurate. The result showed that Google Translate accurately translates English polysemous words. However, as not all the accuracy of the part of speech reaches 100%, Google Translate users still need to recheck the translation output and post edit so that the translation accuracy of the polysemous word can reach 100%.